The Effect of Using Probing Prompting Learning Model on Students’ Speaking Ability (at the Eleventh grade of SMK Negeri 1 Barus Utara in 2020/2021 Academic Year) - pierre jordan simanjuntak (JURNAL LINER (Language Intelligence and Educational Research), 2022)
Abstract : The purpose of this research are to found out: 1) The application of probing-prompting learning model on students’ speaking ability, 2) The students’ speaking ability before and after using probing-prompting model, 3) whether there is any significant effect of probing-prompting learning model on students’ speaking ability at the Eleventh Grade of SMK Negeri 1 Barus Utara.This research uses experimental method with the pre-experimental design by using one-group pretest and posttest design. The population of this research is the XI Grade students’of SMK Negeri 1 Barus Utara which consist of 71 students and the samples were 28 students gotten by using purposive sampling. In collecting the data, the researcher used observation sheet. Instrument of the research was observation and test was oral test. The result of the research are 1) application of probing-prompting learnig model was 3.7, it was categorized “very good”. 2) The mean score of the students’ before using probing-prompting learning model was 51, it was categorized “bad”. Meanwhile after using probing-prompting learning model was 59, it was categorized “bad”. 3) The result of analysis showed that ttest is bigger than ttable (ttest12.4> ttable 2.05). So, the hypothesis was accepted. It means that there is any significant effect of probing-prompting learning model on students’ speaking ability at the Eleventh Grade of SMK Negeri 1 Barus Utara. Keywords: Probing Prompting Learning Model, Speaking